Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Disiplin Guru di SMK Kesehatan Bhakti Nusantara, Banjar Agung Kabupaten Tulang Bawang Provinsi Lampung - Khomsinnudin Khomsinnudin (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The education management paradigm in improving quality effectively and efficiently requires educational human resources (HR) which will later support improving the quality of education, the competence of qualified teachers is a very important factor. With educators who have high disciplinary loyalty and also school principals who play a good role in institutional institutions. This study aims to find out the role of the principal in improving teacher discipline at Kesehatan Bahkti Nusantara Banjar AgungTulang Bawang Vocational School. This study uses a descriptive qualitative approach which is intended to study and analyze data found in the field and then described in sentences and words. Data collection techniques used observation, interviews, and documentation from teachers and school principals. The results of this study are that the principal who acts as a leader has a strong influence in increasing teacher discipline in school institutions.